The influence of audit committee chair characteristics on financial reporting quality - Abdalwali Lutfi; Saleh Zaid Alkilani; Mohamed Saad; Malek Hamed Alshirah; Ahmad Farhan Alshira'h; Mahmaod Alrawad; Malak Akif Al-Khasawneh; Nahla Ibrahim; Abeer Abdelhalim; Mujtaba Hashim Ramadan (Journal of Risk and Financial Management, 2022)
This study examines the extent to which the characteristics of the audit committee chair enhance the quality of financial reports and reduce the possibility for companies to receive a modified audit opinion (MAO) from an external auditor. We apply logistic regression to investigate the influence of Audit Committee Chair (ACC) characteristics on the FRQ (FRQ), for a sample of 460 firm-year observations (service and industrial company listed) on the Amman stock exchange for the years 2017-2020. This study uses the MAO as a proxy for Financial Reporting Quality (FRQ). The results of this study confirmed that the characteristics of the chair of the audit committee have significant and clear impacts on the quality and efficiency of financial reports, which is in line with previous studies that have addressed this topic. The results also indicated that researchers, academics, regulators, and policymakers should not look just at the characteristics of audit committees as a whole, given that audit committee chairs have effects on financial reports. This study presents its contribution through experimental demonstration of the characteristics of the chair of the audit committee and how these affect the financial reports of companies. It also provides a guide for benefits for working to provide a basis for organizational procedures, especially those related to the impact on corporate boards and internal and external auditing.
Keywords: 650; Jordan; audit committee; Audit Committee Chair; auditor; Financial Reporting Quality